FAKTOR DETERMINAN KONDISI OBESOGENIK DAN PERILAKU MAKAN REMAJA URBAN JAKARTA (PENDEKATAN SOSIO-EKOLOGI) - Khasanah, Tri Ardianti; Avicena, Rasyid; Agestika, Lina; Rizqiawan, Angga (UHAMKA PRESS, 2024)
Indonesia is classified as having a high risk of obesity in school-age children and adolescents who are predicted to become obese by 2030. This study aimed to identify the determinant factors of obesogenic conditions and eating behavior of urban Jakarta adolescents using a socio-ecological approach. This research was carried out using descriptive-analytical methods in the urban area of ​​Jakarta. The population in this study was teenagers aged 15 – 19 years. The research results showed that 36.45% were male, and 63.55% were female. Subjects aged 15-17 years were 85.98% and 18-19 years old were 14.02%. As many as 66.34% of subjects had good nutritional status, and 33.64% had more nutritional status. Obesogenic conditions in the form of 24-hour recall results and SQ-FFQ results where energy intake is mostly less by 49.53%, protein intake is mostly more by 55.14%, fat intake is mostly less by 53.74%, and carbohydrate intake was mostly less with 64.02%. As for eating behavior, it was found that aspects of nutritional knowledge were mostly poor at 54.7%, nutritional attitudes were mostly positive at 50.5%, adolescent eating practices were mostly positive at 56.1%, and food availability was mostly good at 51.9%. The conclusion from this research is that the majority of subjects have good nutritional status, their eating patterns and food consumption are still unhealthy. Lack of energy and carbohydrates, as well as high protein consumption, reflect an unbalanced diet influenced by an obesogenic environment. Low nutritional knowledge is an important factor that needs to be corrected to improve adolescent eating patterns. This research shows that to overcome obesity among adolescents, interventions are needed that include nutritional education, access to healthy food, and changes in the obesogenic environment at school and home.